A Preliminary Exploration of People's Democracy in the Whole Process: the CPC's Practice of Building Democratic Power in the Central Revolutionary Base Areas - Wang, Jingyao (Transactions on Social Science, Education and Humanities Research, 2023)
In the Central Revolutionary Base Areas, influenced by the Soviets of the USSR and absorbing its own experience of revolutionary construction, the CPC applied the democratic system for the first time to the process of constructing a new type of regime, creating a preliminary form of people's democracy throughout the entire process under the leadership of the Party. The various aspects of democracy are interlinked, forming a closed loop of rational and relatively complete procedures for people's participation in the practice of democracy. The democratic political system established by the Party in the central revolutionary base areas provides a deep historical foundation for the development of people's democracy in the new era of socialism with Chinese characteristics, leaving behind valuable experience.